1999
DOI: 10.4141/a98-091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish silage and fish fat on growth performance and sensory quality of growing-finishing pigs

Abstract: Kjos, N. P., Skrede, A. and Øverland, M. 1999. Effects of dietary fish silage and fish fat on growth performance and sensory quality of growing-finishing pigs. Can. J. Anim. Sci. 79: 139-147. Thirty-six growing-finishing pigs, with an average initial weight of 24.8 kg ± 2.6 SD, were allocated to six groups to determine the effect of fish silage and fish fat in the diet on performance, carcass characteristics and sensory quality. The treatments were either a control diet, or one of three diets containing 50 g k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
3
19
0
1
Order By: Relevance
“…Thus, diet A with concentrated fish silage at 50 g kg -1 contained 1.8 g kg -1 fish fat. The average content of the fatty acids C20:5 n-3, C22:5 n-3 and C22:6 n-3 in residual fat in fish silage was 16.6, 2.9 and 1.2%, respectively, while the corresponding values for fat separated from fish silage was 15.1, 2.9 and 1.3% (Kjos et al 1999). The DM content (Table 2) was 903 g kg -1 in the control diet, and averaged 898 g kg -1 when fish silage was included (diets A, B, C and D).…”
Section: Composition Of Fish Silage and Dietsmentioning
confidence: 88%
See 2 more Smart Citations
“…Thus, diet A with concentrated fish silage at 50 g kg -1 contained 1.8 g kg -1 fish fat. The average content of the fatty acids C20:5 n-3, C22:5 n-3 and C22:6 n-3 in residual fat in fish silage was 16.6, 2.9 and 1.2%, respectively, while the corresponding values for fat separated from fish silage was 15.1, 2.9 and 1.3% (Kjos et al 1999). The DM content (Table 2) was 903 g kg -1 in the control diet, and averaged 898 g kg -1 when fish silage was included (diets A, B, C and D).…”
Section: Composition Of Fish Silage and Dietsmentioning
confidence: 88%
“…Following heating to 95°C, the fish silage was passed through a decanter and a centrifuge to separate the fat from the defatted fish silage (Jangaard 1987). The processing method is described by Kjos et al (1999).…”
Section: Fish Silagementioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that visceral waste of fish alone contributes to around 3,00,000 t (Mahendraker, 2000). Fish silage is reported to have high nutritional value with all the essential amino acids (Vidotti et al, 2003), which can be used as a high value protein source for feeding different animals such as broilers (Al-Marzooqi et al, 2010), pigs (Kjos et al, 1999), laying hens (Kjos et al, 2001), sheep (Rahmi et al, 2008), fish (Borghesi et al, 2008) and laying quails . Several studies have been reported on production of fermented fish silage from marine fish offals using jaggery and Lactobacillus planatrum inocula (Babu et al, 2005;Samaddar and Kaviraj, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown however that wet fish byproducts can become a valuable protein source in animal feeds if converted into silage. Ensiling the fresh by-products in combination with other locally available feeds rich in fermentable carbohydrates, such as sugar cane molasses, is a simple and appropriate method of conservation (Samuels et al, 1992;Kjos et al, 1999;Zahar et al, 2002). A study by Thuy et al (2010) carried out in the Mekong Delta showed that catfish by-products can be successfully ensiled with 20-40% of sugar cane molasses and preserved for 1-2 months without affecting the quality.…”
Section: Introductionmentioning
confidence: 99%